Evoking Apparent Moving Sensation in the Hand via Transcutaneous Electrical Nerve Stimulation - Scarpelli, Alessia; Demofonti, Andrea; Terracina, Francesca; Ciancio, Anna Lisa; Zollo, Loredana (Frontiers in Neuroscience, 2020)
The restoration of sensory feedback in amputees plays a fundamental role in the prosthesis control and in the communication on the afferent channel between hand and brain. The literature shows that Transcutaneous Electrical Nerve Stimulation (TENS) can be a promising non-invasive technique to elicit sensory feedback in amputees, especially in the lower limb through the phenomenon of Apparent Moving Sensation (AMS). It consists of delivering a sensation that moves along a specific part of the body. This study proposes to use TENS to elicit tactile sensations and adopt AMS to reproduce moving sensations on the hand, such as those related to an object moving in the hand or slipping upward or downward. To this purpose the developed experimental protocol consists of two phases: (i) the mapping of the evoked sensations; (ii) the generation of the AMS. In the latter phase, the Pulse Amplitude Variation (PAV), the Pulse Width Variation (PWV) and the Inter-Stimulus Delay Modulation (ISDM) methods were compared. For the comparative analysis the Wilcoxon-Mann-Whitney test with Bonferroni correction (P<0.016) was carried out on the Success Rate and on the ranking of methods expressed by the subjects. Results from the mapping protocol show that the delivered sensations were mostly described by the subjects as almost natural and superficial tingling. Results from the AMS protocol show that, for each movement direction, the Success Rate of ISDM method is higher than PWV and PAV and significantly higher than PAV for the ulnar-median direction. It recreates an AMS in the hand that effectively allows discriminating the type of sensation and distinguishing the movement direction. Moreover, ISDM was ranked by the subjects as the favourite method for recreating a well-defined and comfortable moving sensation only in the median-ulnar direction. For the ranking results there was not a statistically significant difference among the methods. The experiments confirmed the good potential of recreating an AMS in the hand through TENS. This encourages to push forward this study on amputees and integrate it in the closed-loop control of a prosthetic system, in order to enable full control of grasp stability and prevent the objects from slippage.